2014
DOI: 10.1002/ece3.998
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity in a small population: the case of Chilean blue whales

Abstract: It is generally assumed that species with low population sizes have lower genetic diversities than larger populations and vice versa. However, this would not be the case for long-lived species with long generation times, and which populations have declined due to anthropogenic effects, such as the blue whale (Balaenoptera musculus). This species was intensively decimated globally to near extinction during the 20th century. Along the Chilean coast, it is estimated that at least 4288 blue whales were hunted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 108 publications
2
38
0
Order By: Relevance
“…Torres-Florez et al [44] also noted haplotype diversity within the species is higher than might be expected considering the recent whaling impact, and hypothesized that this might be due to some degree of past sub-structuring. They suggest that the relatively high diversity seen in the Chilean blue whales (0.890) relative to pygmy blue whales [45] off Australia may be due to long-term feeding ground site fidelity along the coast (as suggested by the present study) despite the lack of evidence for genetic sub-structure.…”
Section: Discussionmentioning
confidence: 99%
“…Torres-Florez et al [44] also noted haplotype diversity within the species is higher than might be expected considering the recent whaling impact, and hypothesized that this might be due to some degree of past sub-structuring. They suggest that the relatively high diversity seen in the Chilean blue whales (0.890) relative to pygmy blue whales [45] off Australia may be due to long-term feeding ground site fidelity along the coast (as suggested by the present study) despite the lack of evidence for genetic sub-structure.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were collected under the ethics requirements of the country, as detailed elsewhere [7,9]. rsbl.royalsocietypublishing.org Biol.…”
Section: Discussionmentioning
confidence: 99%
“…In the Northern Hemisphere, there is one subspecies (B. m. musculus), and in the Southern Hemisphere, there are two subspecies: the pygmy blue whale (B. m. brevicauda), which feeds in temperate waters, and the Antarctic blue whale (B. m. intermedia), which feeds in Antarctic waters. The lowest recorded genetic diversity in populations of blue whales is found in pygmy blue whales that feed off Australia [4][5][6][7] (table 1). Traditional genetic analyses have indicated that Australian pygmy blue whales have undergone a genetic bottleneck at an unknown time [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species has been slow to recover from almost total decimation and hence a valuable discovery was made in 1993, when a small blue whale population of 232 individuals was found in the Gulf of Corcovado in the Chiloense Ecoregion of Southern Chile (Hucke-Gaete et al 2004). Genetic, acoustic and morphometric studies indicate that these blue whales are part of a wider Southeast Pacific population that is distinct from both the Antarctic (B. musculus intermedia) and "pygmy" (B. musculus brevicauda) blue whale subspecies (Branch et al 2007, Buchan et al 2014, Torres-Florez et al 2014. Further investigations are required to establish the degree of isolation of the population and the health and viability of the individuals within it.…”
Section: Introductionmentioning
confidence: 99%